PENGARUH METODE STRATAGEM MELALUI PEMBELAJARAN KOOPERATIF TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 20 PADANG - Alfi Yunita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The goal of this research was to know: “Was the students’ understanding of mathematics concept who were taught by using ‘Stratagem’ Method through cooperative learning better than conventional Method.” The research method was Quasi Experimental Research, Post-test Only Control Design. Data was collected from the test. From data data analysis, it was found that the students’ understanding of mathematics concept who were taught by using ‘Stratagem’ Method through cooperative learning was better than conventional Method. Kata kunci: metode stratagem, pembelajaran kooperatif, pemahaman konsep matematis